2018
DOI: 10.3390/met8050323
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intermetallic Particles on the Corrosion Properties of Extruded ZK60 Mg Alloy Containing Cu

Abstract: The microstructure and corrosion behavior of the extruded ZK60 Mg alloys with different Cu content were comparatively investigated. The ZK60 alloy had a microstructure consisting of α-Mg grains with intermetallic MgZn 2 and Zn 2 Zr 3 particles. The addition of 1 wt % Cu resulted in the additional presence of CuMgZn particles. In a 0.6 M NaCl solution at 25 • C, the corrosion rate of the alloy with the added Cu appeared to be about 16% faster than that of the alloy without the addition of Cu. The factors affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, the effect of the second phase in ZK60 alloys on their corrosion behaviors is barely reported. Some researchers tried to enhance the corrosion resistance of ZK60 alloys by modifying their microstructure through heat treatment [ 30 , 31 ], deformation processing [ 32 ], and alloying [ 33 , 34 , 35 , 36 ]. Even so, the relationship between the microstructure and corrosion behavior of ZK60 alloys needs more studies for it to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of the second phase in ZK60 alloys on their corrosion behaviors is barely reported. Some researchers tried to enhance the corrosion resistance of ZK60 alloys by modifying their microstructure through heat treatment [ 30 , 31 ], deformation processing [ 32 ], and alloying [ 33 , 34 , 35 , 36 ]. Even so, the relationship between the microstructure and corrosion behavior of ZK60 alloys needs more studies for it to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, due to the high intrinsic reactivity of Mg, the potential difference between the second phases and α-Mg matrix will cause galvanic corrosion. These second phases formed in ZWCK6100 alloy with combined addition of Cu and Y, such as CuMgZn and I (Mg 3 Zn 6 Y) phases, are nobler than α-Mg matrix [16] and will act as cathodes and accelerate the corrosion rate. The volume fraction of CuMnZn phase is very low, because the addition amount of Cu is 0.5 wt-%, combustion loss is inevitable in the smelting process, and some Cu atoms replace Mg atoms in I phase [25].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that Cu is one of the most important alloying elements for Mg alloys. On the one hand, Cu can improve the age hardening ability of Mg–Zn-based alloy by promoting the precipitation of MgZn 2 phases, and the mechanical properties of Mg–Zn, Mg–Zn–Al and Mg–Zn–Zr alloys have been significantly elevated by Cu addition [9,16-18]. On the other hand, the eutectic temperature of Mg–Zn alloys can be enhanced by Cu, permitting the use of a higher solution treatment temperature [19].…”
Section: Introductionmentioning
confidence: 99%
“…A strong micro-galvanic effect was observed between the Mg-α and MgZn 2 second-phase particles precipitated at grain boundaries. Baek et al [9] have also observed that intermetallic particles played a major role in the corrosion behavior of the ZK60 alloy in sodium chloride solution due to microgalvanic effects between the anodic Mg-α matrix and precipitates containing zinc and zirconium.…”
Section: Introductionmentioning
confidence: 97%